Green approach for the decoration of Pd nanoparticles on graphene nanosheets: an in situ process for the reduction of C-C double bonds and a reusable catalyst for the suzuki cross-coupling reaction - Hussain, Najrul; Borah, Ashwini; Darabdhara, Gitashree; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (New Journal of Chemistry, 2015)
A new strategy for in situ synthesis of palladium nanoparticles (Pd NPs) decorated on reduced graphene oxide (rGO) nanosheets with controlled size and shape is reported. This strategy was designed as three processes in one pot, namely, (a) reduction of graphene oxide, (b) formation of Pd NPs on the rGO nanosheets and (c) simultaneous reduction of olefin. In this synthesis process, a hydrogen atmosphere was used to develop the Pd NPs-rGO nanocatalyst, which is reusable and easily separable. The influence of the size and morphology of the Pd-rGO-H-2 catalyst on the catalytic activity in the Suzuki cross-coupling reaction was investigated by comparing with other catalysts, Pd-rGO-As and Pd-rGO-Gl, and they were synthesized by different reducing agents, ascorbic acid and glucose, respectively. The catalysts were characterized by electron microscopy (HRTEM, SEM), FT-IR, XRD and XPS. The Pd-rGO-H-2 catalyst was found to possess excellent catalytic activity and recyclability in the Suzuki cross-coupling reaction under mild reaction conditions.

Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2015)
Highly stable Cu(0) nanoparticles were synthesized on reduced graphene oxide (rGO) sheets using a cost-effective and green method. The synthesized Cu(0)-nanoparticle-rGO composites exhibit excellent catalytic activity for the synthesis of symmetrical biaryls from arylboronic acids under microwave irradiation. The reaction proceeds smoothly in base-free conditions with easy recovery and reuse of the catalyst. The methodology is compatible with various functional groups and provides an attractive protocol for the synthesis of symmetrical biaryls with very good yields. HRTEM, XPS and XRD analyses showed the catalyst to be recyclable. The Cu(0) nanoparticles are stable in the rGO nanosheets, and the particle size distribution and oxidation state of the Cu(0) nanoparticle remain the same after performing the chemical reaction.

Glucose-derived porous carbon-coated silicon nanowires as efficient electrodes for aqueous micro-supercapacitors - Devarapalli, Rami Reddy; Szunerits, Sabine; Coffinier, Yannick; Shelke, Manjusha V.; Boukherroub, Rabah (ACS Applied Materials & Interfaces, 2016)
In this study, we report on carbon coating of vertically aligned silicon nanowire (SiNWs) arrays via a simple hydrothermal process using glucose as carbon precursor. Using this process, a thin carbon layer is uniformly deposited on the SiNWs. Under optimized conditions, the coated SiNWs electrode showed better electrochemical energy storage capacity as well as exceptional stability in aqueous system as compared to uncoated SiNWs. The as-measured capacitance reached 25.64 mF/cm(2) with a good stability up to 25000 charging/discharging cycles in 1 M Na2SO4 aqueous solution.
Keywords: carbon coating; glucose precursor; hydrothermal; microsupercapacitors; silicon nanowires

Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions (vol 5, pg 1251, 2015) - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2016)
Correction for ‘Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions’ by Najrul Hussain et al., Catal. Sci. Technol., 2015, 5, 1251–1260.

Glory of fire retardants in Li-ion batteries: could they be intrinsically safer? - Mishra, Rajat; Anne, Mounika; Das, Sayan; Chavva, Tarunikaa; Shelke, Manjusha V.; Pol, Vilas G. (Advanced Sustainable Systems, 2024)
Lithium-ion batteries (LIBs) have dramatically transformed modern energy storage, powering a wide range of devices from portable electronics to electric vehicles, yet the use of flammable liquid electrolytes raises thermal safety concerns. Researchers have investigated several ways to enhance LIB's fire resistance. Fire retarding molecules functions through cooling effects, scavenging radicals, and forming protective barriers. Incorporating fire-suppressing molecules within the LIBs aims to delay or mitigate thermal runaway scenarios, reducing the risks of fires or explosions. Achieving an optimal balance between safety and performance is a major obstacle in the design of intrinsically safer LIBs. Therefore, it is important to consider their effects on LIB's performance, long-term stability, and environmental impact. To overcome these challenges, collaborative research efforts among academia, industry, and regulatory sectors are necessary. This article reviews state-of-the-art literature associated with LIBs safety or even fire mitigation by introducing solid-state or quasi-solid-state electrolytes as well as modified liquid electrolytes. Moreover, the effectiveness of various strategies in making LIBs intrinsically safer is critically evaluated with an emphasis on fire retardants followed by shedding some light on the remaining challenges.